Critical ranges for leaf nitrogen and potassium levels in coffee fertigated at the production phase - Assis, Gleice; Guimarães, Rubens; Colombo, Alberto; Scalco, Myriane; Dominghetti, Anderson (Revista Ciência Agronômica, 2014)
With the aim of establishing critical ranges for the leaf nitrogen (N) and potassium (K) levels in fertigated coffee crops under production, an experiment was carried out in the experimental area of the Sector for Coffee Cultivation of the Department of Agriculture at the Federal University of Lavras, in Brazil. Treatments consisted of five levels of fertilizer applied through fertigation: 30%, 80%, 130%, 180% and 230% of the recommended amounts of N and K for rainfed coffee grown in Minas Gerais. A randomised block design with four replications was used. Critical ranges for nutrient concentrations in the leaves were established from the results of growth characteristics (plant height and stem diameter), leaf analyses and productivity. The results obtained were: a) nitrogen (g kg-1): 32.39 to 32.40 for January/February; 33.60 to 33.61 for March/April; 27.39 to 27.42 for May/June; 24.23 to 24.24 for July/August; 26.06 to 26.09 for September/October and 26.50 to 26.51 for November/December; b ) potassium (g kg-1): 20.08 to 20.14 for January/February; 17.89 to 17.91 for March/April; 15.93 to 15.96 for May/June; 15.29 to 15.35 for July/August; 16.61 to 16.64 for September/October and 20.58 to 20.64 for November/December.